Assessment of social losses of pollution's health caused by man-made pollution of atmospheric air with emissions of particulate matters (PM10). - Turos, Ye. I.; Petrosian, A. A.; Davidenko, A. N. (Medicni Perspektivi, 2017)
According to available estimates, about 3% of lethal outcomes from cardiac-pulmonary pathology and 5% from lung cancer are related to the impact of patriculate matters (PM). In the course of the study there were assessed social losses of population’s health (additional death cases) caused by risk conditions of atmospheric air pollution with PM of various air-dynamic diameter (PM10), proper to emissions of various industrial enterprises. It was established that 90% of population of cities under study live under high exposures (≥50 µg/m3) health and risks for population (IRM=10-3÷10-4), caused by PM10emissions. Results showed that metallurgical industry is responsible for 7,2 to 2193 additional mortality cases. The impact of machine building enterprises – from 0.06 to 21 cases; coke and chemical – from 1.5 to 36 cases; mining – from 1.1 to 14,6 cases. The findings revealed 0.6 % increase in lifetime mortality for each 10 µg/m3 in 24-hour average PM10 concentration. Based on research outcomes, a set of instruments was developed for implementation of air pollution risk management programs aimed at mitigation of health risks from (PM10) in highly exposed groups.